Multifrequency Investigation of Single-and Double-Stranded DNA with Scalable Metamaterial-Based THz Biosensors - Weisenstein, Christian; Richter, Merle; Wigger, Anna Katharina; Boßerhoff, Anja Katrin; Bolivar, Peter Haring (Biosensors, 2022)
Due to the occurrence of THz-excited vibrational modes in biomacromolecules, the THz frequency range has been identified as particularly suitable for developing and applying new bio-analytical methods. We present a scalable THz metamaterial-based biosensor being utilized for the multifrequency investigation of single-and double-stranded DNA (ssDNA and dsDNA) samples. It is demonstrated that the metamaterial resonance frequency shift by the DNA’s presence depends on frequency. Our experiments with the scalable THz biosensors demonstrate a major change in the degree of the power function for dsDNA by 1.53 ± 0.06 and, in comparison, 0.34 ± 0.11 for ssDNA as a function of metamaterial resonance frequency. Thus, there is a significant advantage for dsDNA detection that can be used for increased sensitivity of biomolecular detection at higher frequencies. This work represents a first step for application-specific biosensors with potential advantages in sensitivity, specificity, and robustness.
CRIS-Team Scopus Importer:2022-08-05
Keywords: biomolecular; biomolecules; biosensor; DNA; FSS; metamaterial; sensitivity; sensor; terahertz; THz